PSYCHOLOGICAL CONDITIONING OF STUDENTS IN ARABIC LEARNING THROUGH ONLINE GAME MODELS - Akla, Akla; Handayana, Sri (IMLA (Arabic Teacher and Lecturer Association of Indonesia), 2022)
This study aims to analyze (a) the process of learning Arabic using online games , (b) the psychological condition of students before and after using online games, (c) students' Arabic skills .This study model uses a Mixed-Method. Research respondents were class V MIN 1 Metro and MIN 1 Lampung Timur students, which collected 70 students from each Madrasah. The data collection tool used in this study consisted of three instruments, namely interviews, questionnaires, and tests. The findings of this study that 99.4% of students respond with positive behavior when using online games, and only 0.6% of students respond with negative behavior. Furthermore, using online games improves the psychological condition of students at MIN 1 Metro by 64.75% and at MIN 1 East Lampung students by 64.39%. In addition, the use of online games has increased learning outcomes in Arabic by 39.00% for MIN 1 Metro students and 36.38% for MIN 1 students in East Lampung.